Chloroplast-derived photo-oxidative stress causes changes in H2O2 and EGSH in other subcellular compartments. Issue 1 (6th January 2021) - Ugalde, José Manuel; Fuchs, Philippe; Nietzel, Thomas; Cutolo, Edoardo A; Homagk, Maria; Vothknecht, Ute C; Holuigue, Loreto; Schwarzländer, Markus; Müller-Schüssele, Stefanie J; Meyer, Andreas J
Abstract: Metabolic fluctuations in chloroplasts and mitochondria can trigger retrograde signals to modify nuclear gene expression. Mobile signals likely to be involved are reactive oxygen species (ROS), which can operate protein redox switches by oxidation of specific cysteine residues. Redox buffers, such as the highly reduced glutathione pool, serve as reservoirs of reducing power for several ROS-scavenging and ROS-induced damage repair pathways. Formation of glutathione disulfide and a shift of the glutathione redox potential ( E GSH ) toward less negative values is considered as hallmark of several stress conditions. Here we used the herbicide methyl viologen (MV) to generate ROS locally in chloroplasts of intact Arabidopsis ( Arabidopsis thaliana ) seedlings and recorded dynamic changes in E GSH and H2 O2 levels with the genetically encoded biosensors Grx1-roGFP2 (for E GSH ) and roGFP2-Orp1 (for H2 O2 ) targeted to chloroplasts, the cytosol, or mitochondria. Treatment of seedlings with MV caused rapid oxidation in chloroplasts and, subsequently, in the cytosol and mitochondria. MV-induced oxidation was significantly boosted by illumination with actinic light, and largely abolished by inhibitors of photosynthetic electron transport. MV also induced autonomous oxidation in the mitochondrial matrix in an electron transport chain activity-dependent manner that was milder than the oxidation triggered in chloroplasts by the combination of MV and light. In vivo redox biosensing resolves the spatiotemporal dynamics of compartmental responses to local ROS generation and provides a basis for understanding how compartment-specific redox dynamics might operate in retrograde signaling and stress acclimation in plants. Abstract : Methyl viologen-induced photo-oxidative stress increases hydrogen peroxide and oxidation of glutathione in chloroplasts, cytosol, and mitochondria, as well as autonomous oxidation in mitochondria.